Spatial distribution of crimes in urban areas : an insight from Sri Lanka - Wickremasinghe, Hashini T.; Kaluthanthri, P. C. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Similar to other Asian countries, it is forecasted that the urban population in Sri Lanka will continue to increase at an accelerating rate and the majority will be living in urban areas by 2022. Urban crime which is a major challenge that cities face is assumed to spread with the increasing population. They are clustered geographically generating a substantial economic struggle. The related theories argue that criminal opportunity is the root cause of crime and physical environmental design makes an influence on the criminal opportunity. Therefore, a need of identifying how the built environment and different land uses become an opportunity and make an impact on the spatial distribution of urban crimes is evident. This study aims to do a hotspot analysis within the Colombo Municipal Council Area, Sri Lanka to identify the spatial relationship of urban crimes with different land uses. The data on 627 crime incidents occurred in 2018 were obtained from crime records of police stations in Colombo North, South and Central police divisions and were analyzed using Kernel Density Estimation in Geographical Information Systems (GIS) software. As per study findings, seven wards were identified as crime hotspots. Further, findings reveal that robbery and drug arrest incidents are common around low-income residential housing areas while property theft records are common around hospitals, cinemas and concentrated commercial areas. Vehicle thefts are often recorded near lakes, offices and playgrounds whereas housebreakings are recorded near housing schemes. Finally, implications to mitigate these impacts were also presented.